2015
DOI: 10.1097/j.pain.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pain processing in individuals with cognitive impairment

Abstract: Cognitive impairment (CI) can develop during the course of ageing and is a feature of many neurological and neurodegenerative diseases. Many individuals with CI have substantial, sustained, and complex health care needs, which frequently include pain. However, individuals with CI can have difficulty communicating the features of their pain to others, which in turn presents a significant challenge for effective diagnosis and treatment of their pain. Herein, we review the literature on responsivity of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 117 publications
2
77
1
1
Order By: Relevance
“…Patients with dementia have been reported to express pain differently than cognitively intact elderly patients in that they seem to have an elevated/increased pain experience [35,36,37] and tend to rate pain lower than their cognitively intact peers [37,38]. Alternatively, they may express pain by changes in behavior instead of verbal communication, and it may be that patients with dementia have been treated with an antipsychotic instead of analgesics, but this calls for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with dementia have been reported to express pain differently than cognitively intact elderly patients in that they seem to have an elevated/increased pain experience [35,36,37] and tend to rate pain lower than their cognitively intact peers [37,38]. Alternatively, they may express pain by changes in behavior instead of verbal communication, and it may be that patients with dementia have been treated with an antipsychotic instead of analgesics, but this calls for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pain represents a clinical challenge in cognitively impaired and demented patients both in its assessment as well as treatment [1,2,3]. In the case of Alzheimer's disease (AD), the most common dementia in the elderly, clinical evidences warn that pain is grossly undertreated in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Alzheimer's disease (AD), the most common dementia in the elderly, clinical evidences warn that pain is grossly undertreated in these patients. The scientific consensus estimates that several factors contribute to this management: (1) The increased pain co-morbidity in aging; (2) The reduced selfreport due to the poor verbal communicative abilities that worsen with the progress of the disease until being completely absent; (3) The complex progressive nature of the neurodegenerative disorder [2,3]. It is known that the sensory-discriminative dimension of pain, which depends on the lateral nociceptive pathway, is prehttp://dx.doi.org/10.1016/j.neulet.2015.06.007 0304-3940/© 2015 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Three independent reviewers (BS, TT, MS) performed electronic database searches using EMBASE (1974 to present), MEDLINE (1946 to present) and PsycINFO (1967 [18] studies were also considered for potentially relevant articles.…”
Section: Information Sources and Search Detailsmentioning
confidence: 99%
“…A previous narrative review [18] of the experimental pain literature in AD concluded that the research is equivocal but proposed that pain sensitivity does not appear to be reduced in AD versus HCs. Whilst this narrative review, conducted by experts in the field, was helpful and advanced the field, some pertinent questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%